Barleria acuminata Extract-Mediated Organic–Inorganic Copper Phosphate Nanohybrids: Synthesis, Optimization and Antioxidant Potential - Palaskar, R.; Shinde, K.; Dhokane, D.; Nimbalkar, M.; Belhekar, A.; Jadhav, U. (Asian Journal of Chemistry, 2026)
In the present study, we report the green synthesis of Barleria acuminata extract mediated copper phosphate nanohybrids (BAE-CuPNHs) by a simple one-pot co-precipitation approach. Aqueous extracts of six different Barleria species were prepared by using ultrasonication and microwave-assisted extraction methods and evaluated for total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity. Among the tested species, B. acuminata showed highest phytochemical content and DPPH radical scavenging activity and was selected for nanohybrid preparation. The formation of nanohybrid was screened for different metal ions. Copper ions formed well-defined flower-like nanostructures with high efficiency of phytochemical immobilization. Optimization studies showed 4 mM CuSO4, 2.0 mL PBS, static incubation and an incubation period of 72 h as the optimum conditions for the synthesis. FESEM, EDX, FTIR and XRD characterization confirmed the formation of crystalline BAE-CuPNHs with marigold-like morphology. The synthesized BAE-CuPNHs displayed antioxidant activity, indicating their promising prospects for antioxidant delivery and bioactive applications.